Setdb1 ablation in macrophages attenuates fibrosis in heart allografts - Zhibo Ma; Xi Zhou; Wenlong Jia; Xiaosheng Tan; Xia Huang; Jingzeng Wang; Lingjuan Sun; Qingwen Li; Xiangli Zhao; Naonao Yuan; Ping Liu; Jing Liu; et al. (Proceedings of the National Academy of Sciences, 2025)
Tissue fibrosis is commonly associated with organ malfunction and is strongly associated with the development of chronic rejection, cardiovascular diseases, and other chronic diseases. Fibrosis also contributes to immune exclusion in tumor tissues. Targeting fibrosis might be a strategy for prolonging allograft survival while suppressing cancer development. Here, single-cell transcriptomes of human and mouse heart allografts showed that macrophages accumulated in grafts with fibrosis were reprogrammed via histone methylation regulated by Setdb1, an H3K9 methyltransferase. Myeloid-specific deletion of Setdb1 prolonged heart allograft survival but reversed immune exclusion in tumor tissues. Interestingly, myeloid-specific Setdb1-knockout led to lower fibrosis in heart allografts and tumor tissues in mice. Our single-cell sequencing data showed that Setdb1 ablation impaired Fn1 + and SPP1 + profibrogenic macrophage reprogramming. Mechanistically, Fn1, which was induced by the CCR2-Creb/Setdb1 axis, upregulated the expression of genes related to fibrosis in fibroblasts and macrophages via ITGA5 and PIRA receptors. Blocking the interaction between FN1 and these receptors inhibited fibrosis in allograft and tumor tissues. Our results reveal a target, histone methylation in macrophages, for the treatment of fibrosis-related disease.